Harnessing the Potential of Synbiotic Therapy for Childhood Malnutrition: A Narrative Review of Onion Inulin Extracts and Probiotic-Rich Dadih - Rahmaddiansyah, Refa; Rahmi, Wahida; Arisanty, Dessy; Rita, Rauza Sukma; Rusti, Sukarsi (Faculty of Medicine, Universitas Andalas, 2024)
Background: Childhood malnutrition stems from inadequate intake and disease; synbiotics (probiotics+prebiotics) can modulate gut microbiota and immune function, aligning with SDG-3 targets through cost-effective prophylaxis and immunomodulation. Objective: To evaluate onion (Allium cepa Linn.)-derived inulin combined with probiotic-rich Sumatran dadih as supportive therapy for pediatric malnutrition. Methods: Narrative literature review of human and relevant preclinical studies on synbiotics, inulin, dadih, gut microbiota, and immune modulation, with selection based on relevance and methodological quality. Results: Evidence suggests synbiotics improve microbiota diversity, short-chain fatty acid production, nutrient absorption, and reduce inflammation and infection rates. Onion-inulin functions as a fermentable prebiotic; dadih provides robust local lactic-acid bacteria strains. Yet data are heterogeneous, sample sizes small, and dosing/formulation poorly standardized; safety reporting is variable. Conclusion: An onion-inulin + dadih synbiotic is a plausible, context-appropriate adjuvant for managing childhood malnutrition. Rigorous, controlled trials should optimize dose, strain selection, and formulation, and confirm efficacy and safety for scalable implementation.